Factors Affecting Utilization of Communication Sources by the Farmers of Jammu & Kashmir - Y.S. Bagal , L.K. Sharma and J.S. Manhas (Indian Journal of Extension Education, 2018)
The study was carried out to find out the socio-economic characteristics of farmers affecting the utilization ofvarious communication sources in Samba district of Jammu and Kashmir state of India. A multistage randomsampling technique was used for drawing a total sample of 120 respondents. The data was collected througha well-structured interview schedule. The study showed that average age of the respondent was 57.04 years;nearly one-fourth of respondents were illiterate; majority of the respondents (83%) were having telephoneconnectivity and average operational land holding of the respondents was 1.74 hectares. Educational level,telephone connectivity and irrigation availability were significantly affecting the awareness, utilization andperceived effectiveness of different communication sources. Less sharing of information among farmers;distant location of agricultural university; method demonstrations, field days, kissan melas, exhibitions, resultdemonstration were not organized on a regular basis; having less time to use mass media sources and illiteracyof the respondents were the major problems in using mass media and interpersonal communication sources